Pengaruh Kualitas Produk dan Harga Terhadap Kepuasan Pelanggan UD Brontoseno Nganjuk - Septian Andika Pratama (Journal of Management and Social Sciences, 2023)
This study aims to determine the effect of product quality (X1) and price (X2) on customer satisfaction (Y) at UD. Brontoseno Nganjuk. This type of quantitative research Data collection techniques used are primary data and secondary data. The sample selection used the accidental sampling method, the number of samples was 75 respondents at UD. Brontoseno Nganjuk. The analysis technique used is validity test, reliability test, classic assumption test, multiple linear regression analysis, t test, F test and coefficient of determination test. From the results carried out in the study, it showed that product quality (X1) and price (X2) variables on customer satisfaction (Y) at UD. Brontoseno NganjukThe research results obtained multiple linear regression equation Y = 3.230 + 0.193X1 + 0.481X2 and the results of the t-test variable product quality have a partially significant effect on customer satisfaction. Price has a significant effect partially on customer satisfaction. The results of the F test obtained Fcount results with a significance value of 0.000 <0.05. From the results of the analysis it can be concluded that Product Quality and Price have a simultaneous and significant effect on UD Customer Satisfaction. Brontoseno Nganjuk.